With six you get eggroll [videorecording (DVD)] - Morris, Howard, 1919-2005; Day, Doris, 1922-2019-; Keith, Brian, 1921-1997; Carroll, Pat, 1927- (Paramount widescreen DVD collection, 2005)
A widow with three sons and a widower with a daughter elope and then must deal with the antagonism of their children and even their dogs.